THE EFFECT OF FAMILY OWNERSHIP AND CEO DUALITY ON COMPANY PERFORMANCE WITH POLITICAL CONNECTIONS AS MODERATOR VARIABLES - Prasti, Tiara Vindra; Bararoh, Tantri; Inayati, Titik (Journal of Industrial Engineering & Management Research, 2022)
This study aims to examine and analyze the effect of family ownership and CEO duality on firm performance with political connection as a moderation variable in manufacture companies listed in Indonesia Stock Exchange. This research uses purposive sampling model with multiple linier regressions method and moderated regressions. Research sample was 274 manufacture companies listed on Indonesia Stock Exchange. The research period is 2016-2020. The results of the study explain that family ownership has significant effect on the performance of manufacture companies. The results also explain that CEO duality has significant effect on the performance of manufacture companies. On the effect of mediation, the results of the study explain that political connection significantly strengthens the positive effect of family ownership dan CEO duality on firm performance.